Consequences of the IPPC-directive's BAT requirements for abatement costs and emissions - Jan Larsson; Kjetil Telle (Statistics Norway, Research Department, 2005)
The Integration Pollution and Prevention Control (IPPC) directive from the European Union implies that the regulatory emission caps should be set in accordance with each industry's Best Available Techniques (BAT). The directive is under implementation in Norway, and it represents a refocus of the Norwegian environmental regulations away from economic efficiency towards a BAT principle. We examine the effect of this implementation with respect to expected emission reductions and increases in costs. Data Envelopment Analyses (DEA) is used to construct a frontier of all efficient plants. This provides us with two alternative interpretations of BAT. First, we assume that all the plants emit in accordance with the best practice technology, represented by the frontier, by reducing all inputs proportionally. Second, we assume that all plants emit in accordance with the best practice technology by reducing emissions only. Both interpretations reveal substantial potential for emission reductions. Further, abatement cost estimates indicate that considerable emission reductions can be achieved with low or no social costs, but that the implementation of BAT for all plants involves substantial costs.
Keywords: D21; K23; K32; L61; L65; L73; Q48; R38; 330; IPPC; BAT; Emissions; Energy intensive industries; DEA; Technical efficiency; Frontier technology.